2018
DOI: 10.1021/acssuschemeng.7b04733
|View full text |Cite
|
Sign up to set email alerts
|

Production of Value-Added Composites from Aluminum–Plastic Package Waste via Solid-State Shear Milling Process

Abstract: Aluminum–plastic multilayer films have been widely used in the packaging industry, but the recycling of such a material is a great challenging task. Herein, we reported a facile route to produce value-added composites with high thermal conductivity and high electrical insulation from aluminum–plastic package waste (APPW) for the first time. Briefly, solid-state shear milling (S3M) technology was applied to prepare ultrafine APPW powder and exfoliate expandable graphite (EG) into graphite nanoplatelets (GNPs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 57 publications
3
30
0
Order By: Relevance
“…During the MM process, the shearing action leads to a certain decrease in the relative molecular mass of UHMWPE, but also promotes the increase e e ective thermal conductivities of two-phase polymeric composites have been predicted by many researchers via proposing theoretical and empirical models. Hereon, Agari's semi-empirical model [41][42][43][44][45] can t better results than other models. e logarithmic equation of Agari is shown as follows:…”
Section: 5mentioning
confidence: 93%
“…During the MM process, the shearing action leads to a certain decrease in the relative molecular mass of UHMWPE, but also promotes the increase e e ective thermal conductivities of two-phase polymeric composites have been predicted by many researchers via proposing theoretical and empirical models. Hereon, Agari's semi-empirical model [41][42][43][44][45] can t better results than other models. e logarithmic equation of Agari is shown as follows:…”
Section: 5mentioning
confidence: 93%
“…The development of composites that exhibit thermal and electrical insulation properties became an interesting alternative to reuse residues, as reported by Yang and co‐workers. [ 149 ] Authors studied composites of graphite nanoplatelets and aluminum plastic package waste that presented 29 MPa of tensile strength for 35 vol% of graphite, as well as 1.7 W/m K of thermal conductivity and 10 −10 S/cm of electrical conductivity.…”
Section: Municipal Solid Wastesmentioning
confidence: 99%
“…The development of composites that exhibit thermal and electrical insulation properties became an interesting alternative to reuse residues, as reported by Yang and coworkers. [149] Authors studied composites of graphite nanoplatelets and aluminum plastic package waste that presented 29 MPa of tensile strength for 35 vol% of graphite, as well as 1.7 W/m K of thermal conductivity and 10 −10 S/cm of electrical conductivity. Furthermore, Yang [150] has also demonstrated that the use of expanded graphite into composites with plastic package waste allowed it to have isotropic thermal conductivity and efficient electromagnetic interference shielding effectiveness.…”
Section: Package and Plastics Wastesmentioning
confidence: 99%
“…From the engineering application point of view, both nanosized noble metal and graphene faced some bottlenecks including complex preparation process and high cost. On the other hand, little attention has been focused on the use of cheap metal filler with a high aspect ratio and a high thermal conductivity (e.g., aluminum flake, 240 W/mK) to resolve this problem, although the surface self-passivation nature of aluminum (Al) may have the potential to prepare insulating thermal conductivity composite.…”
Section: Introductionmentioning
confidence: 99%
“…The desired composite with a continuous insulating thermal conductive network was then prepared by powder mixing and thermal molding. First, considering the environmental sustainability, a flaky polymer powder was prepared from multilayer plastic package waste (MPW) through solid-state shear milling (S3M) technology. ,, Afterward, oxidized Al nanoflake is coated on the surface of the flaky MPW particles during powder mixing, then continuous filler network is fabricated by following compression molding of MPW paticles. This oxidized Al network can act as a thermal conductive pathway for heat transfer and maintained electrical insulation due to the Al 2 O 3 layer.…”
Section: Introductionmentioning
confidence: 99%